2005
DOI: 10.1111/j.1525-1497.2005.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of nonadherence to screening colonoscopy

Abstract: Background: Colonoscopy has become a preferred colorectal cancer (CRC) screening modality. Little is known about why patients who are referred for colonoscopy do not complete the recommended procedures. Prior adherence studies have evaluated colonoscopy only in combination with flexible sigmoidoscopy, failed to differentiate between screening and diagnostic procedures, and have examined cancellations/no‐shows, but not nonscheduling, as mechanisms of nonadherence. Methods: Sociodemographic predictors of scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
229
5
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(247 citation statements)
references
References 18 publications
11
229
5
2
Order By: Relevance
“…Most studies that examine preventive CRC screening do so aiming to find the problem -e.g., patient barriers, [25][26][27][28][29][30] physician barriers, [5][6][7]31,32] system barriers [14,23,24,33,34] -and implement targeted interventions that solely impact CRC screening. These approaches, while successful to varying degrees, may be limited in their usefulness in applied practice settings for a number of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies that examine preventive CRC screening do so aiming to find the problem -e.g., patient barriers, [25][26][27][28][29][30] physician barriers, [5][6][7]31,32] system barriers [14,23,24,33,34] -and implement targeted interventions that solely impact CRC screening. These approaches, while successful to varying degrees, may be limited in their usefulness in applied practice settings for a number of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…We first identified a framework on the barriers and facilitators to screening from the studies included in this review (Garcia-Dominic et al, 2012), supplemented by two other frameworks by Christy et al and Denberg et al, which focused on masculinity (avoidance of femininity, self-reliance, risk taking and heterosexual self-presentation) and screening procedure respectively, to form a more comprehensive meta-framework (Christy et al, 2014;Denberg et al, 2005). This meta-framework was then pilot tested by two researchers against ten studies before the final framework was decided.…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…1 Other studies found that fear of intraprocedural pain and embarrassment were significant barriers to compliance with a colonoscopy examination. 2,3 In contrast, healthcare professionals may prioritize safety, ease of colonoscopy completion, and rapid and complete cognitive recovery to facilitate early discharge. Arguably, both lighter and deeper sedation can potentially achieve these goals.…”
Section: Résumémentioning
confidence: 99%